Efficacy of sotrastaurin plus tacrolimus after de novo kidney transplantation: randomized, phase II trial Results - Russ, Graeme R.; Tedesco-Silva, H.; Kuypers, D. R.; Cohney, S.; Langer, R. M.; Witzke, O.; Eris, J.; Sommerer, Claudia; von Zur-Mühlen, B.; Woodle, E. S.; Gill, J.; Ng, J.; et al. (European journal of pain, 2013)
Sotrastaurin, a novel immunosuppressant, blocks early T cell activation through protein kinase C inhibition. Efficacy and safety of sotrastaurin with tacrolimus were assessed in a dose-ranging non-inferiority study in renal transplant recipients. A total of 298 patients were randomized 1:1:1:1 to receive sotrastaurin 100 (n = 77; discontinued in December 2011) or 200 mg (n = 73) b.i.d. plus standard tacrolimus (sTAC; 5-12 ng/mL), sotrastaurin 300 mg (n = 75) b.i.d. plus reduced tacrolimus (rTAC; 2-5 ng/mL) or enteric-coated mycophenolic acid (MPA) plus sTAC (n = 73); all patients received basiliximab and corticosteroids. Composite efficacy failure (treated biopsy-proven acute rejection ≥ grade IA, graft loss, death or loss to follow up) rates at Month 12 were 18.8%, 12.4%, 10.9% and 14.0% for the sotrastaurin 100, 200 and 300 mg, and MPA groups, respectively. The median estimated glomerular filtration rates were 55.7, 53.3, 64.9 and 59.2 mL/min, respectively. Mean heart rates were faster with higher sotrastaurin doses and discontinuations due to adverse events and gastrointestinal adverse events were more common. Fewer patients in the sotrastaurin groups experienced leukopenia than in the MPA group (1.3-5.5% vs. 16.5%). Sotrastaurin 200 and 300 mg had comparable efficacy to MPA in prevention of rejection with no significant difference in renal function between the groups.
Gesehen am 24.01.2022